The learning and teaching of Occupational Safety and Health Management module: KUKUM’s experience - Azuddin, Bahari, Lt Kol (B); Kamal Bahrin, Baharuddin (Kolej Universiti Kejuruteraan Utara Malalaysia, 2008)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 17th - 18th December 2005 at Asenia Hotel Resort, Langkawi.